Effect of Hydrothermal Carbonization on the Properties, Devolatilization, and Combustion Kinetics of Chilean Biomass Residues - Cubillos-Montecino, F; Diaz-Robles, L; Campos-Bravo, V; Vallejo-Gallardo, F (Elsevier Ltd, 2019)
This work evaluates the hydrothermal carbonization (HTC) process as a method to upgrade the quality of biomass residues to be used as fuels in gasification or combustion processes. Seven residues from Chilean biomass were characterized thermochemically before and after being processed by HTC. Additionally, the kinetics of devolatilization and combustion were studied. HTC produces biomass with lower ash content, higher carbon content and higher heating value than the original biomass. Herbaceous wastes showed lower heating values (LHV) around 20% higher after HTC process, while increases around 10% in woody and agroindustrial wastes and corn (even being herbaceous wastes) were observed. The chlorine values obtained after HTC indicate the possibility of using the herbaceous, woody and industrial wastes studied as fuels without chlorine related problems. The activation energy (Ea) values from cellulose and hemicellulose decomposition were higher after HTC process, while lower Ea values from lignin decomposition were found. The combustion characteristic temperatures, ignition temperature (Ti), peak temperature (Tp), and burnout temperature (Tb), were delayed towards higher temperatures with HTC process for all residues. Moreover, the reactivity (R) and combustibility index (S) were lower after HTC, indicating slower combustion for the samples after HTC. Finally, the results show that HTC is a promising process to homogenize the kinetic parameters and the combustion behavior of the samples, thus increasing the interchangeability of the samples in combustion or gasification systems. © 2019 Elsevier Ltd